Contribution of Ultra-Fine Bubbles to Promoting Effect on Propane Hydrate Formation - Uchida, Tsutomu; Miyoshi, Hiroshi; Sugibuchi, Ren; Suzuta, Akio; Yamazaki, Kenji; Gohara, Kazutoshi (Frontiers in Chemistry, 2020)
To investigate experimentally how ultra-fine bubbles (UFBs) may promote hydrate formation, we examined the formation of propane (C3H8) hydrate from UFB-infused water solution using two preparation methods. In one method, we used C3H8-hydrate dissociated water, and in the other, C3H8-UFB-included water prepared with a generator. In both solutions, the initial conditions had a UFB number density of up to 109 mL−1. This number density decreased by only about a half when stored at room temperature for 2 days, indicating that enough amount of UFBs were stably present at least during the formation experiments. Compared to the case without UFBs, the nucleation probabilities within 50 h were 1.3 times higher with the UFBs, and the induction times, the time period required for the bulk hydrate formation, were significantly shortened. These results confirmed that UFB-containing water promotes C3H8-hydrate formation. Combined with the UFB-stability experiments, we conclude that a high number density of UFBs in water contributes to the hydrate promoting effect. Also, consistent with previous research, the present study on C3H8 hydrates showed that the promoting effect would occur even in water that had not experienced any hydrate structures. Applying these findings to the debate over the promoting (or “memory”) effect of gas hydrates, we argue that the gas dissolution hypothesis is the more likely explanation for the effect.